UJI PUPUK (NPK dan EMAS) DAN ZAT PENGATUR TUMBUH (ATONIK dan ETHREL) TERHADAP PERTUMBUHAN VEGETATIF TANAMAN LADA (Piper nigrum L) - Djamhari, Sudaryanto (Badan Pengkajian dan Penerapan Teknologi, 2006)
The objective of the research is to know the effect of using NPK (Nitrogen-Phosphor-Potassium) fertilizer and EMAS (Enhancing Microbial Activities in the Soil) biofertizers combined with GRS (Growth Regulating Substances) to the vegetative growth of young pepper plants. The research used Complete Randomized Design with One Way Analysis of Variance, Regression, and Correlation in order to know the effect of treatment to the vegetative growth of young pepper plants. The research was carried out in Sukahati Village, Cibinong District, Bogor Regency, West Java Province, during three months from July to October 2001.The results of the research showed that the use of NPK fertilizer (with dosage 2,5 gr/plant) combined with GRS Atonik and Ethrel will increase the vegetative growth of young pepper plants significantly to a high of 13,0 cm or 17,4 % and 12,5 cm or 16,8 % respectively. The use of EMAS biofertilizer (with dosage 2,5 gr/plant) combined with GRS Atonik and Ethrel will increase the vegetative growth of young pepper plants significantly to a high of 21,2 cm or 28,5 % and 18,1 cm or 24,3 % respectively. Moreover, the use of NPK fertilizer (with dosage 5,0 gr/plant) combined with GRS Atonik and Ethrel will increase the vegetative growth of young pepper plants significantly to a high of 22,2 cm or 29,8 % and 20,3 cm or 27,2 % respectively. The use of EMAS biofertilizer (with dosage 5,0 gr/plant) combined with GRS Atonik and Ethrel will increase the vegetative growth of young pepper plants significantly to a high of 28,2 cm or 37,9 % and 26,6 cm or 35,7 % respectively.